Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/ijc.1421
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow microcirculation analysis in multiple myeloma by contrast-enhanced dynamic magnetic resonance imaging

Abstract: The aim of our study was to investigate the quantitative microcirculation parameters amplitude A (hypothetical intravascular volume) and exchange rate constant k 21 (hypothetical vascular permeability) by contrast-enhanced dynamic magnetic resonance imaging (dMRI) as markers of angiogenesis in multiple myeloma (MM). Therefore lumbar spine and spina iliaca superior posterior of 16 normal controls and 41 patients with active MM were assessed using a dMRI protocol with a pump controlled bolus infusion of Gadolini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
55
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 26 publications
3
55
0
Order By: Relevance
“…Different patterns of bone marrow involvement of MM in conventional as well as DCE-MRI have been described concordantly by different authors (14,23,29,30). Diffuse distribution of microcirculation was found in healthy controls as well as in all stages of plasma cell disease.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Different patterns of bone marrow involvement of MM in conventional as well as DCE-MRI have been described concordantly by different authors (14,23,29,30). Diffuse distribution of microcirculation was found in healthy controls as well as in all stages of plasma cell disease.…”
Section: Discussionsupporting
confidence: 53%
“…To visualize the distribution of microcirculation parameters in the examined area, a colorcoded pharmacokinetic map is superimposed onto the static MR image. DCE-MRI parameters amplitude A and exchange rate constant kep are significantly increased in patients with active MM compared with healthy controls and correlate with osteolytic bone involvement and prognosis (14). Earlier work of our group shown in 24 myeloma patients the significant correlation of high Amplitude A of DCE-MRI with increased micro vessel density (15).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…5 Dynamic contrastenhanced magnetic resonance imaging (DCE-MRI) is a noninvasive technique to assess changes in microcirculation associated with cancer in various tissues. [6][7][8] In prior studies, we have demonstrated that DCE-MRI as a functional imaging technique highly correlates with histologically determined bone marrow angiogenesis in MM. 9 The quantitative results obtained with DCE-MRI do not only reflect increased blood vessel density described by Amplitude A (A) but also increased vessel permeability represented by exchange rate constant kep (kep).…”
mentioning
confidence: 99%
“…10 Evaluation of color coded maps superimposed on conventional MR images permits differentiation of 4 distinct microcirculation patterns. 6,11,12 It is largely unknown, however, which genetic features in myeloma cells induce the angiogenic change in microcirculation (''angiogenic switch''). 13 Schreiber et al demonstrated an increased micro vessel density detected by immunhistochemical staining of CD34 in bone marrow samples of MM patients with deletion 13q14.…”
mentioning
confidence: 99%